Evaluation of Natural Fertilizer Potential of Neem Leaves Aqueous Extract for Irrigation Practices - K. A. Mohammed; O. S. Balogun; K. R. Adebayo (Journal of Applied Sciences and Environmental Management, 2023)
A natural fertilizer relies on plant, mineral and animal sources for its nutrients. The objective of this paper is to evaluate the natural fertilizer potential of Neem leaves aqueous extract for irrigation practices by analyzing some physicochemical parameters using standard methods. Data obtained shows that the pH level were, 8.4, 7.2, 7.1, and 7.3 respectively   indicating a moderate alkalinity status suitable for irrigation. The electrical conductivity values were as 2.4, 2.2, and 1.8 mg/L for Neem aqueous extract while turbidity values were 334, 323, and 296 NTU respectively .These values are within the acceptable range according to FAO guidelines. SAR values were as 11.20, 10.04, and 10.81 and chloride levels were found to be; 22.1, 16.12, and 5.97 mg/L, posing no concerns for irrigation. Sodium levels were 35.7, 27.32 and 25.31 mg/L which also falls within the FAO guidelines and indicating moderate sodicity. Overall, the nutritional compositions of the Neem leaf extracts were within the FAO guideline limits for irrigation fluid, indicating their suitability for irrigation practices. This Neem leaf extract as an irrigation solution could provide a valuable insights for farmers and agricultural practitioners seeking to optimize crop productivity and quality.